2004
DOI: 10.1002/rcm.1767
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of phenolic acids and flavonoids in dandelion (Taraxacum officinale WEB. ex WIGG.) root and herb by high‐performance liquid chromatography/electrospray ionization mass spectrometry

Abstract: Phenolic acids and flavonoids were extracted from a dandelion (Taraxacum officinale WEB. ex WIGG.) root and herb juice and characterized by high-performance liquid chromatography/electrospray ionization mass spectrometry. Among the 43 compounds detected, 5 mono- and dicaffeoylquinic acids, 5 tartaric acid derivatives, 8 flavone and 8 flavonol glycosides were characterized based on their UV spectra and their fragmentation patterns in collision-induced dissociation experiments. The predominant compound was chico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
147
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 200 publications
(166 citation statements)
references
References 43 publications
18
147
1
Order By: Relevance
“…Therefore, the differences observed for antioxidant activity of the samples are related to the amount of phenolic compounds and not with the phenolic compounds profile, which is similar ( Table 3). Schütz et al (2005) also reported chicoric acids as the main phenolic compounds found in dandelion (Taraxacum officinale). Indeed, chicoric acids are relevant secondary metabolites in plants of the tribe Cichorieae (family Asteraceae), including genus Taraxacum or Lactuca, being used for taxonomic purposes (Schütz et al, 2005).…”
Section: Antioxidants Contributionmentioning
confidence: 92%
See 2 more Smart Citations
“…Therefore, the differences observed for antioxidant activity of the samples are related to the amount of phenolic compounds and not with the phenolic compounds profile, which is similar ( Table 3). Schütz et al (2005) also reported chicoric acids as the main phenolic compounds found in dandelion (Taraxacum officinale). Indeed, chicoric acids are relevant secondary metabolites in plants of the tribe Cichorieae (family Asteraceae), including genus Taraxacum or Lactuca, being used for taxonomic purposes (Schütz et al, 2005).…”
Section: Antioxidants Contributionmentioning
confidence: 92%
“…Schütz et al (2005) also reported chicoric acids as the main phenolic compounds found in dandelion (Taraxacum officinale). Indeed, chicoric acids are relevant secondary metabolites in plants of the tribe Cichorieae (family Asteraceae), including genus Taraxacum or Lactuca, being used for taxonomic purposes (Schütz et al, 2005). Williams et al (1996) and Gatto et al (2011), using different extraction and analysis methods, reported similar results on flowers and leaves of T. officinale.…”
Section: Antioxidants Contributionmentioning
confidence: 92%
See 1 more Smart Citation
“…Taraxacum officinale (common dandelion) and Taraxacum kok-saghyz (Russian dandelion) are members of the Asteraceae and therefore possess articulated laticifers (Esau, 1965;Evert, 2006) that secrete a latex rich in polyphenols (Schü tz et al, 2005; C. Schulze Gronover, unpublished data). T. kok-saghyz latex is a good source of high-molecular-weight rubber (Mooibroek and Cornish, 2000;Bushman et al, 2006) and was investigated as an alternative to H. brasiliensis during World War II, when rubber supplies to Europe and the United States were interrupted.…”
mentioning
confidence: 99%
“…It provides a powerful approach to characterize and identify a variety of polar and thermally labile compounds such as flavonoids in crude extracts of plants (Wang et al 2004;Schutz and others 2005;Tai et al 2006;Guo et al 2007;Ren et al 2007;Zheng et al 2007;Avul et al 2008;Liu et al 2008). Various hyphenated and hybrid mass spectrometers have now become widely adopted, and, among them, TimeOf-Flight (TOF) MS and its hybrid or in combination use with Tandem Mass Spectrometry (MS/MS) have proven to be very powerful tools for the structural characterization of natural compounds in view of their complementary capacity to provide multistage fragmentations and accurate mass measurements for precise elemental compositions of molecular ions and subsequent product ions (Schutz et al 2005;Ferrer et al 2004;Yokosuka et al 2006;Zhu et al 2007). Recently, Liquid Chromatography Electrospray Ionization source in combination with hybrid Ion Trap and high-resolution Time-of-flight Mass Spectrometry (LC-(ESI)-IT-TOF/MS) has been successful in the identification and characterization of compounds in various fields Gao et al 2008).…”
Section: Introductionmentioning
confidence: 99%